The Effect of Women's Autonomy in the Uptake of Long-Acting and Permanent Contraception Methods among Women Reproductive Age in East Kalimantan - Annisa Nurrachmawati syaiful bahri; Ike Anggreini G; Mugia Bayu Raharja; Dewi Endah Ramadhani (STIKes Hang Tuah Pekanbaru, 2020)
Background: Despite decreased fertility rate, East Kalimantan Province still facing unmet needs. Moreover, almost all contraceptive use in East Kalimantan depends on short-acting contraceptive methods. Only a few studies have ever been conducted on women's autonomy in relation to Long-Acting Permanent Contraception Methods (LAPMs) choices. It is, therefore, essential to find the associated factors affecting LAPMs uptake. This study aimed to analyze the influence of sociodemographic, knowledge, women's autonomy and fertility on LAPMs uptake at the household level. Methods: The data derived from the Indonesian Demographic and Health Survey (IDHS) 2017 of East Kalimantan Province. As much as 570 women of childbearing age (10–49 years) with marital status who still using contraception in any method was included as samples. Results: Factors correlate with the uptake of LAPMs in the bivariate analysis were age, insurance ownership, family planning knowledge and women's autonomy (p value<0.05). While in the multivariate analysis only women autonomy and insurance ownership were related to the uptake of LAPMs. Conclusion: This finding provides evidence for including women empowerment programs in the family planning program. Keywords: Family planning, women autonomy, long acting contraceptive methods